Evaluation of soil structure interaction effects on structural performance of historical masonry buildings considering earthquake input models - Gent, Ali Fuat; Atmaca, Esin Ertuerk; Guenaydin, Murat; Altunisik, Ahmet Can; Sevim, Baris (ELSEVIER SCIENCE INC, 2023)
Consideration of the soil domain is significant in the evaluation of seismic response. Since, the wave propagation, soil amplifications, and deformability of subsoil significantly affect the seismic response of structures. For this reason, the effect of soil-structure interaction and soil condition should be considered in the evaluation of the seismic response of structures. This paper presents a seismic performance evaluation of a historical masonry building considering different soil conditions and earthquake input models. The building investigated in this study dates back to the 1870 s. The seismic performance of the building was evaluated with a new guideline specifically published for the assessment of historical structures. At the end of the analyses, natural frequencies, mode shapes, maximum displacements, and principal stresses were obtained and presented in detail. In terms of drift ratio control, the building showed only limited damage during the applied earthquake record. Also, in general, the requirement for the stresses was satisfied. This means that the building behaved in a linear response. While the natural frequency values decreased from the hard soil condition to the soft soil condition, the drift ratios increased for each earthquake input model. The maximum differences between natural frequencies ob-tained from massless-soil and massed-soil SSI systems increased from the hard soil to soft soil conditions. It was concluded that the soil models with mass or without mass did not affect the frequencies too much in the hard soil condition, but it was quite effective in medium and soft soil conditions. It was clearly seen that there were differences between the results obtained from earthquake input models based on different soil conditions. In this context, it should be noted that the soil-structure interaction of historical masonry structures sensitive to seismic effects should be considered depending on different earthquake input models. As a matter of fact, it was thought that it is necessary to contribute to the studies available in the literature in this field.
Keywords: Earthquake input model; Historical masonry structures; Soil -structure interaction; Seismic response; DAMAGE ASSESSMENT; DEFORMABILITY; MECHANISMS; Engineering